Patterns of Population and Urban Growth in Southwest Europe: 1920-2010 - Chatel, Cathy [UNESP]; Morillas-Torné, Mateu; Esteve, Albert; Martí-Henneberg, Jordi (SAGE Publications, 2017)
This work seeks to measure, locate, and explain changes in the distribution of population and urban growth in the territory formed by France, Italy, and the Iberian Peninsula between 1920 and 2010. This is based on population data of more than fifty-six thousand local units obtained from population censuses: The Geokhoris database that we built. Our starting viewpoint is that it is only possible to understand the extent of the urbanization process within the context of the evolution of all of the municipalities. The description of the distribution and growth of population at the local level shows the population concentration in the various urban agglomerations, and, since 1970, a relative deconcentration and extension of the cities. Within this context, a regression model helped us to identify the geographic factors that correlate with these fundamental transformations in population geography, which were also indicative of new forms of social organization within the territory.
Keywords: database; linear regression; population change; southwestern Europe; urbanization